Formula Extraction of Open Hysteresis in Supreme Theory of Everything - Tarzad , Ulaanbaatar (New Trends in Physical Science Research Vol. 1, 2022)
Not only universe, but everything has general characters as eternal, infinite, cyclic and wave-particle duality. Everything from elementary particles to celestial bodies, from electromagnetic wave to gravity is in eternal motions, which dissects only to circle. Since everything is described only by trigonometry. In this paper the formula extraction of the open hysteresis in Supreme Theory of Everything is shown.